The History of Virginia, in Four Parts - Beverley, Robert (Salt Lake City, UT : Project Gutenberg, 2010)
"The History of Virginia, in Four Parts" by Robert Beverley is a historical account written in the early 18th century. The book details the establishment and development of Virginia, with a focus on the early settlements, interactions with Native Americans, and the evolution of its government. It presents a narrative rich in detail about the trials and tribulations faced by the settlers, the resources of the land, and the cultural practices of the indigenous populations. At the start of the historical narrative, Beverley recounts the initial attempts to settle Virginia, beginning with Sir Walter Raleigh's expeditions and the discovery of the region. He describes the enticing nature of the land, the favorable accounts of the climate and resources brought back by early explorers, and the intent of these expeditions to capitalize on the perceived riches and opportunities Virginia offers. The narrative highlights the complexities of relationships with Native Americans, detailing their hospitality as well as the growing tensions that emerged from English settlers' desires for land and resources. The beginning sets the stage for a detailed exploration of Virginia's history, including governance, trade, and cultural dynamics experienced by its inhabitants. (This is an automatically generated summary.)
I. The history of the first settlement of Virginia, and the government thereof, to the year 1706 -- II. The natural productions and conveniences of the country, suited to trade and improvement -- III. The native Indians, their religion, laws and customs, in war and peace -- IV. The present state of the country, as to the polity of the government, and the improvements of the land the 10th of June 1720.
Release date is 2010-06-06
E-text prepared by Julia Miller, Christine Aldridge, and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://www.archive.org/details/americana)
Keywords: Virginia -- History -- Colonial period, ca. 1600-1775; Indians of North America -- Virginia -- Early works to 1800; Virginia -- Description and travel -- Early works to 1800